Comparison of the indocyanine green dye method versus the combined method of indigo carmine blue dye with indocyanine green fluorescence imaging for sentinel lymph node biopsy in breast conservative therapy for stage ≤IIA breast cancer - Nobuyuki Takemoto; Ai Koyanagi; Masanori Yasuda; Hiroshi Yamamoto (BMC Women's Health, 2018)
Abstract Background Fluorescence imaging (FI) is one of the methods to identify sentinel lymph nodes (SLNs). However, the procedure is technically complicated and requires procedural skills, as SLN biopsy must be conducted in dim light conditions. As an improved version of this method, we introduced a combined method (Combined mixed dye and fluorescence; CMF) consisting of indigo carmine blue dye and FI. The direct visualization of SLNs under shadowless surgical light conditions is facilitated by the addition of the blue dye. We compared the SLN detection rates of CMF with that of the indocyanine green (ICG) dye method (ICG-D). Methods A total of 202 patients with stage ≤IIA breast cancer who underwent breast conservative therapy with separate incision from January 2004 to February 2017 were reviewed. Details of the two methods are as follows: (1) ICG-D: 10 mg of ICG was used and the green-stained SLNs were resected via a 3-4 cm axillary incision; (2) CMF: A combination of 5 mg of ICG and 4-8 mg of indigo carmine was used. After a 1.5–2 cm incision was made near the point of disappearance of the fluorescence using Photodynamic Eye (PDE), the blue-stained SLNs were resected under shadowless surgical light conditions. Results There were 92 ICG-D and 110 CMF cases. CMF resulted in a significantly higher SLN detection rate than ICG-D (96.4% vs. 83.7%; p = 0.003). This difference was particularly notable in those aged ≥60 years (98.3% vs. 74.3%) and individuals with body mass index (BMI) ≥25 kg/m2 (90.3% vs. 58.3%). Conclusion CMF is an effective method to identify SLNs which is safe and efficient. CMF achieves a high SLN identification rate and most of this procedure is feasible under shadowless surgical light conditions. CMF can reliably perform SLN biopsy even in those aged ≥60 years and individuals with BMI ≥ 25 kg/m2.